The genomic landscape of nonsmall cell lung carcinoma in never smokers. Issue 11 (10th December 2019) - Boeckx, Bram; Shahi, Rajendra B.; Smeets, Dominiek; De Brakeleer, Sylvia; Decoster, Lore; Van Brussel, Thomas; Galdermans, Daniella; Vercauter, Piet; Decoster, Lynn; Alexander, Patrick; Berchem, Guy; Ocak, Sebahat; et al.
Abstract : Lung cancer is the number one cause of cancer‐related death worldwide with cigarette smoking as its major risk factor. Although the incidence of lung cancer in never smokers is rising, this subgroup of patients is underrepresented in genomic studies of lung cancer. Here, we assembled a prospective cohort of 46 never‐smoking, nonsmall cell lung cancer (NSCLC) patients and performed whole‐exome and low‐coverage whole‐genome sequencing on tumors and matched germline DNA. We observed fewer somatic mutations, genomic breakpoints and a smaller fraction of the genome with chromosomal instability in lung tumors from never smokers compared to smokers. The lower number of mutations, enabled us to identify TSC22D1 as a potential driver gene in NSCLC. On the other hand, the frequency of mutations in actionable genes such as EGFR and ERBB2 and of amplifications in MET were higher, while the mutation rate of TP53, which is a negative prognostic factor, was lower in never smokers compared to smokers. Together, these observations suggest a more favorable prognosis for never smokers with NSCLC. Classification of somatic mutations into six‐substitution type patterns or into 96‐substitution type signatures revealed distinct clusters between smokers and never smokers. Particularly, we identified in never smokers signatures related to aging, homologous recombination damage and APOBEC/AID activity as the most important underlying processes of NSCLC. This further indicates that second‐hand smoking is not driving NSCLC pathogenesis in never smokers. Abstract : What's new? About 15 percent of lung cancers occur in people who never smoked but never smokers are usually underrepresented in genomic studies of lung cancer. Here the authors sequenced a unique cohort of 46 never smokers with non‐small cell lung carcinoma (NSCLC). They identified the transcription factor TSC22D1 as a new potential driver gene of NSCLC and observed higher mutation rates in receptor tyrosine‐protein kinases EGFR HER2 and MET in tumors of never smokers compared to smokers. Targeted agents against each of these 3 genes are available, underscoring the relevance of studying never smokers as a separate group.